Kepemimpinan Pendidikan pada Manajemen Berbasis Sekolah (MBS) - Ika Rifa Rofifah; Sukataman Sukataman (LPPM IAINU Kebumen, 2023)
This study aims to find out how educational leadership is in School Based Management (SBM), starting from the definition, development framework, to the principal's leadership in SBM. This research was conducted using qualitative research. The research method used is library research. The data collection technique used was by finding sources and reconstructing them from various sources, such as books, journals, and the results of previous research on SBM. Data from various references were analyzed using descriptive analysis to support the propositions and ideas in this article.